10-year engagement with Kenyan Agriculture and Environment Ministries leads to uptake of climate smart agriculture practices by over 1 million farmers. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Kenyan farmers are increasingly adopting climate-smart agriculture practices and technologies, bringing significant benefits in farm yields, livestock assets, and household welfare. CSA uptake has been spurred by CCAFS engagement with Kenyan Ministries over the past 10 years to support CSA adoption and implementation. CCAFS is a co-founding partner of the CSA Multi-Stakeholder Platform, aimed at coordinating and expanding CSA activities and investments in Kenya. It is estimated that 1,2 million farmers have adopted CSA practices in Kenya.